ANALYSIS OF THE LEVEL OF WORKER COMPLIANCE IN THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) AT THE LOCOMOTIVE DEPO AND TRAIN DEPO PT. KAI MEDAN - Lubis, Ade Irma Seftyani; Wardani, Liza Putri; Mauliyand, Sarda; Sirait, Salshabila Azzahra; Dewi, Virda Puspa; Syahputra, Aldi; Salianto, Salianto (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Occupational safety and health is an effort to prevent or reduce work accidents through stopping/minimizing risks or hazard factors in order to achieve work targets or creation. Based on data from the International Labor Organization (ILO), every year 2.78 million workers die due to accidents and diseases at work. Based on this number, around 2.4 million (86.3 percent) die from occupational diseases, while more than 380,000 (13.7 percent) from work accidents. Therefore, Personal Protective Equipment (PPE) is a crucial aspect in reducing the level of hazard risk to workers. This study aims to understand the level of compliance of workers wearing PPE at the work site. This research is qualitative research and case study research design. Based on the results of interviews and observations carried out, it is understood that the level of compliance of informants wearing PPE is still fairly moderate, this matter is evident from the informant's statement that there are still many incomplete use of PPE required when working.